Identifikasi Mineral Batuan Mata Air Panas Bukit Kasih Kanonang Menggunakan SEM-EDX dan FTIR - Christina Sorongan; Donny Royke Wenas; Jeilen Gabriela Nikita Nusa; Heindrich Taunaumang; Vistarani Arini Tiwow (Jurnal FisTa Fisika dan Terapannya, 2025)
North Sulawesi has considerable geothermal potential as evidenced by the emergence of several types of geothermal manifestations, one of which is located in Kanonang village, precisely on the hill of Kasih Kanonang. The purpose of this research is to determine the rock structure and type of rock contained in the rock in the manifestation area located on the hill of love kanonang. The method to be used in this research is to analyze in the laboratory using SEM-EDX tools and FTIR tools. The results showed that the mineral content and mineral types of geothermal manifestations of hot springs in kanonang love hill have 3 elements namely Oxygen, Silica, and Aluminum with a percentage content of O 66.60%, Si 31.25%, and Al 0.73%.